Direct and indirect cost of diabetes care among patients with type 2 diabetes in private clinics: a multicenter study in Punjab, Pakistan. (2nd November 2018) - Gillani, Ali Hassan; Aziz, Muhammad Majid; Masood, Imran; Saqib, Anum; Yang, Caijun; Chang, Jie; Mohamed Ibrahim, Mohamed Izham; Fang, Yu
ABSTRACT: Background : Diabetes mellitus (DM) has a very high prevalence and poses a huge financial encumbrance on patients. This study aimed to evaluate the cost of diabetes care among patients with type 2 diabetes in private clinics of southern Punjab, Pakistan. Research design and methods : This was a descriptive, cross-sectional, prevalence-based, cost-of-illness (COI) study conducted in six private clinics of southern Punjab from July to September 2016, using a pretested questionnaire. Study participants were recruited using a random selection method. Continuous variables, including direct and indirect costs, were summarized using descriptive statistics. Inferential statistics were also used to analyze the correlation between the variables and cost. Results : The mean annual direct cost per patient with diabetes was estimated to be 332 USD. Medications accounted for the largest share (60.4%) of this cost. Age, locality, high socioeconomic status, and prolonged disease duration were significantly associated with the direct costs of illness ( p  < 0.05). Moreover, 19% of total earnings among very low-income patients were spent on diabetes care. Conclusions : A substantial proportion of patients' income is spent on diabetes care in Punjab. Our findings support the substantial individual and societal burden caused by diabetes.